2017
DOI: 10.1073/pnas.1713840115
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium internal energy distributions during dissociation

Abstract: In this work, we propose a model for nonequilibrium vibrational and rotational energy distributions in nitrogen using surprisal analysis. The model is constructed by using data from direct molecular simulations (DMSs) of rapidly heated nitrogen gas using an ab initio potential energy surface (PES). The surprisal-based model is able to capture the overpopulation of high internal energy levels during the excitation phase and also the depletion of high internal energy levels during the quasi-steady-state (QSS) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Such parametric models for nonequilibrium conditions are still a current topic of research. 9,11,25 To highlight the performance of different models, a parametric model for transient vibrational and rotational state distributions based on surprisal analysis 9 was applied to Set1. P (v ) and P (j ) distributions for two different sets of temperatures ((T trans = 20000 K, T rovib = 5000 K) and (T trans = 5500 K, T rovib = 20000 K)) from QCT simulation are modelled following the parametrization of Ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such parametric models for nonequilibrium conditions are still a current topic of research. 9,11,25 To highlight the performance of different models, a parametric model for transient vibrational and rotational state distributions based on surprisal analysis 9 was applied to Set1. P (v ) and P (j ) distributions for two different sets of temperatures ((T trans = 20000 K, T rovib = 5000 K) and (T trans = 5500 K, T rovib = 20000 K)) from QCT simulation are modelled following the parametrization of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Such a parametric approach has its foundation in surprisal analysis 24 which was recently used in models for hypersonics. 9,11,25 The reactant state distributions in Set1 are equilibrium distributions and the model functions (Eqs. 2 to 4) were chosen accordingly.…”
Section: Function (F)-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…It was hence found that the NN provides a physically robust model based on validated, microscopic data from which information about nonequilibrium systems can be obtained, obviating the construction of models based on simple, empirical expressions. 165 As the evaluation time of the NN is on the order of seconds for 10 6 state-to-state cross sections, this technique is suitable for direct use in DSMC simulations . The average error from the NN compared with the reference QCT data is ∼ 5 %.…”
Section: Discussionmentioning
confidence: 99%
“…where i is either j or v, f 0 (i; T ) is a Boltzmann distribution, λ 0,i is the normalization constant, λ 1,i is a constant parameter, which controls the extent of depletion and is based on the DMS simulation results 34 . The accuracy of this model will be discussed in the next section.…”
Section: Non-boltzmann Qss Rate Expressionmentioning
confidence: 99%